Faktor-Faktor Penghambat Pembelajaran Seni Budaya (Seni Tari) Di SMP Negeri 4 Padang - Evindo Marsiano; Nerosti Nerosti; Fuji Astuti (FBS Universitas Negeri Padang, 2019)
This article aims to describe the inhibiting factors of the process of learning art and culture, especially in dance teaching materials at SMP N 4 Padang. The type of this research was qualitative using an analytical descriptive approach. Data collection techniques were conducted through observation, interviews, documentation and literature study. Data analysis was done by: data reduction, data presentation and verification of data in conclusion. The results indicated that the inhibiting factors of art and culture learning (dance) at SMP N 4 Padang were: (1) teacher factors, teacher factors which meant that improper use of methods, classroom management, and mastery of teacher material in teaching had an impact on student abilities responding to students in participating in this dance learning. The method given by the teacher did not vary so that students appeared bored and did not care about learning dance so that classroom management became noisy added by the lack of mastery of the material by the teacher, (2) student factors. It could be seen through 3 indicators, namely desire, attention and participation, which could be seen from the first meeting to the third meeting. This could be proven in the first meeting with a percentage of 1.5%. The second meeting was 1.3%, and there was a decrease in the third meeting with a percentage of 1.1%, and (3) the infrastructure facilities used in SMP N 4 Padang in the dance learning process were incomplete, so students' interest in the dance learning activities was low due to space that was not available in the process of learning dance. Thus, the learning process has not been effective.